Patients' perspectives on the development of HIV services to accommodate ageing with HIV: a qualitative study. (April 2018) - Pollard, Alex; Llewellyn, Carrie; Cooper, Vanessa; Sachikonye, Memory; Perry, Nicky; Nixon, Eileen; Miners, Alec; Youssef, Elaney; Sabin, Caroline
The objective of this study was to identify the aspects of healthcare that are most valued by people with HIV and to describe their concerns and preferences for the future delivery of services for non-HIV-related illness. Twelve focus groups of people receiving HIV care were conducted in community settings in South-East England. Groups were quota sampled based on age, gender, sexual orientation and ethnicity. Data were analysed using Framework Analysis. The results showed that among the 74 respondents (61% male), a preference for maintaining all care within specialist HIV clinics was commonplace, but was highest among participants with more extensive histories of HIV and comorbidities. Participants valued care-coordination, inter-service communication and timely updates to medical notes. There were high levels of concern around HIV skills in general practices and the capacity of general practitioners to manage patient confidentiality or deal appropriately with the emotional and social challenges of living with HIV. Participants valued, and had an overall preference for, the specialist knowledge and skills of HIV services, suggesting that non-HIV-specialist services will need to build their appeal if they are to have a greater future role in the care of people with HIV. Particular concerns that should be addressed include: patient confidence in the HIV knowledge and skills of non-specialist service providers; clear processes for prescribing and referrals; improved levels of care-coordination and communication between services and increased patient confidence in the capacity of primary care to maintain confidentiality and to appreciate the stigma associated with HIV.